Change in health related quality of life is different in obese versus non-obese patients with atrial fibrillation after thoracoscopic ablation. (19th May 2022) - Roelofs, MJM; Meulendijks, ER; Wesselink, R; Al-Shama, RFM; De Vries, TAC; Van Boven, WJ; Driessen, AHG; De Groot, JR
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Received research grants (through institution) from Atricure Inc, Bayer, Boston Scientific, Daiichi Sankyo, Johnson&Johnson, Medtronic Received honoraria/speaker/consultancy fees from Abbott, AtriaN Medical, Atricure Inc, Bayer, Biotronik, CVOI, Daiichi Sankyo, IPP Med, Itreas, Medtronic, Novartis, Servier Background: Obesity is an important risk factor for atrial fibrillation (AF), and negatively affects health-related quality of life (QoL) and treatment efficacy. The impact of obesity on the improvement of QoL and on AF recurrence in patients undergoing thoracoscopic AF ablation is unknown. Purpose: To assess the change in QoL and the risk of AF recurrence in obese and non-obese patients with atrial fibrillation undergoing thoracoscopic ablation Methods: Patients undergoing thoracoscopic AF ablation were prospectively included. Holters were performed before and at 3, 6, 9 and 12 months after the procedure. AF recurrence was defined as any atrial tachyarrhythmia episode >30 seconds during one year of follow-up. QoL and AF recurrence rate were assessed for normal weight (BMI ≤ 24, 9 kg/m2), overweight (25, 0 – 29, 9 kg/m2) and obese (≥ 30, 0 kg/m2) patients. QoL was measured by the Short Form 36 questionnaire at baseline and at one year follow-up. Results: Four hundred and eight patients were included for analysis. Six out of eight QoL domains scored lower in obese versus non-obese patients before the procedure. In all patients, six out of eight domains increased after the procedure (p<0.01 for most domains). Obese patients showed a larger improvement of emotional related QoL (p=0.01) and a trend towards a larger improvement of mental QoL (p=0.07), while physical QoL increased similarly to non-obese patients (figure). In obese patients, QoL increased similarly for those with and without AF recurrence (p=0.78), whereas in non-obese patients, AF recurrence was associated with less improvement in mental QoL. AF recurrence at 1-year was similar in all groups (normal weight 72.4%, overweight 68%, obese 70.4%, p=0.692). Conclusion: After thoracoscopic ablation, obese patients have a similar AF freedom rate as non-obese patients, but a greater improvement in mental quality of life, irrespective of AF recurrence status, after thoracoscopic ablation.